Pelatihan Penggunaan Aplikasi Mendeley sebagai Reference Tools Manager dalam Penulisan dan Pengelolaan Karya Tulis Ilmiah - Sadaruddin Sadaruddin; Usman Usman; Hasmawaty Hasmawaty; Syamsuardi Syamsuardi; Muhammad Yusri Bachtiar (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
In the academic world, proper and efficient reference management is essential to ensure the quality and credibility of scientific writing. However, many lecturers and education practitioners, particularly early childhood education teachers, still encounter difficulties in managing references according to established academic standards such as APA and MLA citation styles. This challenge often hinders the process of academic writing and decreases the quality of scholarly outputs. To address this issue, a structured training program was conducted focusing on the use of Mendeley, a digital reference management tool designed to simplify citation and bibliography management automatically. The objective of this training was to enhance participants’ technical competence, digital literacy, and their ability to integrate Mendeley into the process of preparing scientific papers. The training activities were carried out using a series of steps, including needs assessment of participants, collaborative planning, hybrid training implementation (both online and offline), and continuous assistance through follow-up forums. Throughout the program, participants were guided step-by-step on how to install, use, and integrate Mendeley into word processing applications for academic writing. The results of the evaluation showed a significant increase in participants' knowledge and practical skills, with an N-Gain score of 0.70, which falls into the high effectiveness category. The training not only improved the quality of reference management in scientific papers but also promoted greater professionalism and academic accountability. Moreover, it supported the broader goal of integrating technology into educational development. Overall, this initiative is expected to encourage more systematic, efficient, and digitally literate practices in academic writing among educators, ultimately contributing to improved educational quality in higher education settings.